Penerapan Black Box Boundary Value Analysis pada Sistem Penjualan Makanan Berbasis Website - Suciati, Putri Esa; Anggoro, Argo Tri; Keliwawa, Hayartudin; Hakim, Alifia Fatwa; Saifudin, Aries (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
In this web-based food sales application, if there is an error when the customer registers there will be misunderstandings for sellers that can be detrimental. Losses for sellers when the application occurs problems, then online food sales will be disrupted which can reduce product sales and income. In this study to reduce the level of error with website-based sales applications, it is necessary to test or analyze the performance of the application so as not to cause further errors that can be detrimental to the seller and buyer. From several surveys and suggestions finally testing or analyzing food sales applications based on this website applies the Black Box method with one way, namely Boundary Value Analysis. Boundary Value Analysis itself is a technique or way of analyzing that works to test or analyze the amount of value entered in an application that has a battery value.